2018
DOI: 10.3389/fneur.2018.00297
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Injury After Low-Intensity Blast Exposure

Abstract: The increased use of close range explosives has led to a higher incidence of exposure to blast-related head trauma. Exposure to primary blast waves is a significant cause of morbidity and mortality. Active service members and civilians who have experienced blast waves report high rates of vestibular dysfunction, such as vertigo, oscillopsia, imbalance, and dizziness. Accumulating evidence suggests that exposure to blast-wave trauma produces damage to both the peripheral and central vestibular system; similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 60 publications
2
22
0
2
Order By: Relevance
“…Effects of blast shock waves on the middle and inner ear structures were examined. First, consistent with earlier reports ( Lien and Dickman, 2018 in mice; Hickman et al., 2018 in chinchillas), blast exposure ruptured the tympanic membranes of all the 14 blast treated ears, but not the untreated ears. Blast shocks also disrupted the ossicular chain and damaged both the anterior and posterior crus and the front of the footplate of the stapes ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Effects of blast shock waves on the middle and inner ear structures were examined. First, consistent with earlier reports ( Lien and Dickman, 2018 in mice; Hickman et al., 2018 in chinchillas), blast exposure ruptured the tympanic membranes of all the 14 blast treated ears, but not the untreated ears. Blast shocks also disrupted the ossicular chain and damaged both the anterior and posterior crus and the front of the footplate of the stapes ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…While the focus of the study was on effects of blast exposure on vestibular afferent function and the VORs, we performed morphological analyses of the inner ears in three SD rats one week after blast exposure to determine the blast-induced inner ear structural damage and allow comparison to that reported in the literature ( Lien and Dickman, 2018 ). Under deep pentobarbital anesthesia, rats were perfused transcardially first with phosphate buffered saline with pH of 7.4, then with 10% phosphate buffered 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few preclinical studies have reported on vestibular disorders following bTBI. Lien and Dickman investigated vestibular injury following low intensity blast exposure using the rotor rod behavioral task ( 10 ). They found a significant reduction in the ability of the animals to perform the balance task on the rotating rod for several weeks following blast exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Acute vestibulomotor deficits have been noted in 98% of patients diagnosed with bTBI and 72% of these patients report long-term vestibular impairment ( 8 , 9 ). Clinical manifestations of vestibular damage includes motor impairments leading to imbalance, motion intolerance, postural instability and dizziness ( 1 , 10 ). In most cases, there are also significant behavioral concerns that overlap with blast-related impairments such as anxiety, attention, fear, memory, and problem-solving deficits ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%